Ferrous and non-ferrous recycling: Challenges and potential technology solutions. (15th February 2019) - Brooks, Leslie; Gaustad, Gabrielle; Gesing, Adam; Mortvedt, Teija; Freire, Felipe
Highlights: Increasing product complexity metals causes mounting challenges to the scrap industry. Inbound inspection and identification can be improved with technology solutions. Sensor based technologies combined with physical diversion are optimal. Large volume yards gain the most from technical interventions. Abstract: Metals recycling is one of the oldest industries in the United States that now employs over 530, 000 individuals. It has always played a significant role in the economy, supplied extensive goods and services, and the costs and benefits directly and/or indirectly extend worldwide. Improved efficiency in metals recycling is crucial to achieving a more circular economy; to enable this requires understanding how the industry operates and the challenges it must overcome. Increasing metal product diversity and design complexity combined with increased feed volumes has introduced recent additional challenges. This review explores the current status and state of the industry and examines potential technology solutions that address inbound inspection and material identification challenges.